Defense of Human Rights and the Humanitarian Crisis at the Border of Venezuela and Colombia from the United States Policy Perspective - Wordliczek, Rafał (Regional Barometer. Analyses & Prognoses, 2022)
The aim of the article is to present the U.S. policy towards the situation on the border between Venezuela and Colombia in recent years. The main reason for the U.S. involvement was the humanitarian crisis in that area. The causes of the migrant crisis include the Maduro regime’s curtailment of democracy, the sharp drop in oil prices and demand on international markets, and the popular revolt. One of the consequences, besides the obvious, humanitarian ones, unfavorable from the perspective of international security and U.S. interests, is the attempt to destabilize the situation in Colombia and undermine its role in the inter-American world. Colombia is a traditional and loyal U.S. ally in the region. Apart from humanitarian considerations from the perspective of U.S. interests, its activity is dictated by economic, political and strategic reasons related to regional security.